Oligonucleotides—A Novel Promising Therapeutic Option for IBD - Scarozza, Patrizio; Schmitt, Heike; Monteleone, Giovanni; Neurath, Markus F.; Atreya, Raja (Frontiers in Pharmacology, 2019)
Inflammatory Bowel Diseases (IBD), whose denomination comprehends Crohn’s Disease (CD) and Ulcerative Colitis (UC), are intestinal chronic autoimmune diseases that often require lifelong medical therapy. In the last two decades monoclonal antibodies against the cytokine TNF have become integral parts in the treatment of IBD patients, however there are unwanted side-effects and one third of patients show primary non-response while another subgroup loses response over time. Finding novel drugs which could act as target therapies against precise pro-inflammatory molecular patterns to avoid unwanted systemic side effects and additionally the process of immunization, has been the first step leading to subsequent clinical trials. Oligonucleotide based therapies represent a promising novel concept for treatment of IBD. The molecular action of oligonucleotides ranges from inhibition of the translational process of mRNA transcripts of pro-inflammatory molecules, to mimicking bacterial DNA which can activate cellular targets for immunomodulation. Alicaforsen, selectively targets ICAM-1 mRNA. ICAM-1 is an adhesion molecule which is upregulated on endothelial cells during IBD, thereby mediating the adhesion and migration of leucocytes from blood to sites of active inflammation. In CD parental application of alicaforsen did not show therapeutic efficacy in phase II trials, but it demonstrated an improved efficacy as a topical enema in distal UC. Topical application of alicaforsen might represent a therapeutic perspective for refractory pouchitis as well. SMAD7 is a protein that inhibits the signaling of TGFβ, which is the mainstay of a regulatory counterpart in cellular immune responses. An anti-sense oligonucleotide against SMAD7 mRNA (mongersen) demonstrated pre-clinical and phase II efficacy in CD, but a phase III clinical trial was stopped due to lack of efficacy. Cobitolimod is a single strand oligonucleotide, which mimics bacterial DNA as its CpG dinucleotide sequences can be recognized by the Toll-like receptor 9 on different immune cells thereby causing induction of different cytokines, for example IL10 and IFNα. Topical application of cobitolimod has demonstrated efficacy in UC patients. We will also consider two other oligonucleotides which act on the GATA3 transcription factor (SB012) and on carbohydrate sulfotransferase 15 (STNM01) downregulation, which could represent novel promising therapeutic options for the treatment of IBD.